EVALUATION OF CATTLE SHARING SYSTEM IN THE DEVELOPMENT OF CATTLE FARMING FOR THE FARMER GROUPS UNDER NATURAL BOWL FARMING GROUP IN MOJOKERTO REGENCY EAST JAVA - Agus Suwantoro (Journal of Entrepreneurship and Financial Technology, 2023)
The objective of the research cattle sharing program is implemented by the Lembu Alam Farmer Group, an independent community-based institution in Mojokerto, East Java, in terms of farmer income, labor employment and cattle population increase. A survey was conducted using all the55farmers participating in the program from April to June, 2023. Net present value (NPV), benefit cost ratio (BCR) and internal rate of return (IRR) were determined from the conditions of before and after participating in the program. NPV was found to increase for 64.40% from IDR 18,251,432 (before) to IDR 28,338,774 (after). BCR and IRR were 21.35 and 50% respectively. Average income was found to be IDR 5,212,500/year. Cattle natural population increase was found to be 27.05%/year. This program increased the labor employment as much as 12.27%. Regression analysis showed that the factors affected the ability of farmers to give back the share were cattle mortality (P<0.01), farmer experience (P<0.05) and calving interval (P<0.01). It is concluded that this cattle sharing program is a success program in increasing cattle population,